2014
DOI: 10.1017/s0305000914000725
|View full text |Cite|
|
Sign up to set email alerts
|

Attention to the mouth and gaze following in infancy predict language development

Abstract: We investigated longitudinal relations among gaze following and face scanning in infancy and later language development. At 12 months, infants watched videos of a woman describing an object while their passive viewing was measured with an eye-tracker. We examined the relation between infants' face scanning behavior and their tendency to follow the speaker's attentional shift to the object she was describing. We also collected language outcome measures on the same infants at 18 and 24 months. Attention to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
116
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 40 publications
(94 reference statements)
12
116
4
3
Order By: Relevance
“…14 This is also a period of rapid specialization in face 46 and voice 47 recognition along with development of audiovisual speech perception, 48 and, considering that learning is an experience-dependent process, even a small alteration in the type and availability of learning opportunities may have cascading developmental effects. 49,50 Links between overall attention to a social scene in infancy and later developmental outcomes have been reported in typically developing children 51 as well as amongst those with ASD. Specifically, limited orienting to social partners in infancy is associated with later ASD diagnoses amongst high-risk siblings 24-26 and greater severity of autism symptoms amongst clinic-referred toddlers with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…14 This is also a period of rapid specialization in face 46 and voice 47 recognition along with development of audiovisual speech perception, 48 and, considering that learning is an experience-dependent process, even a small alteration in the type and availability of learning opportunities may have cascading developmental effects. 49,50 Links between overall attention to a social scene in infancy and later developmental outcomes have been reported in typically developing children 51 as well as amongst those with ASD. Specifically, limited orienting to social partners in infancy is associated with later ASD diagnoses amongst high-risk siblings 24-26 and greater severity of autism symptoms amongst clinic-referred toddlers with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies, primarily focusing on children with ASD, have assessed relations between individual differences on continuous measures of multisensory attention and language (Patten, Watson, & Baranek, 2014; Righi et al, 2018; Woynaroski et al, 2013; though see Altvater-Mackensen & Grossmann, 2015). Eye-tracking studies with TD children have demonstrated links between attention to the mouth during audiovisual speech and language outcomes (Tenenbaum, Sobel, Sheinkopf, Malle, & Morgan, 2015; Tsang, Atagi, & Johnson, 2018). Using the MAAP, we can now directly assess fine-grained individual differences in three multisensory attention skills and relations with language outcomes, opening the door to understanding developmental pathways.…”
Section: Multisensory Attention and Relations With Languagementioning
confidence: 99%
“…Longitudinal studies have demonstrated that GF is associated with language acquisition and can predict word comprehension and vocabulary (Morales, Mundy, Delgado, Yale, Neal, et al., ; Mundy et al., ; Tenenbaum et al., ). In the period between 6 and 12 months of age, when infants happen to gaze at a face, the frequency of GF is correlated with the amount of attention dedicated to the mouth, an index of ongoing language acquisition (Tenenbaum et al., ).…”
Section: Development Of Gf In the First Yearmentioning
confidence: 99%
“…Longitudinal studies have demonstrated that GF is associated with language acquisition and can predict word comprehension and vocabulary (Morales, Mundy, Delgado, Yale, Neal, et al., ; Mundy et al., ; Tenenbaum et al., ). In the period between 6 and 12 months of age, when infants happen to gaze at a face, the frequency of GF is correlated with the amount of attention dedicated to the mouth, an index of ongoing language acquisition (Tenenbaum et al., ). GF and language acquisition appear to go hand in hand; indeed, the infant's GF between 6 and 18 months of age could predict receptive and expressive language outcomes at 1–2 years of age (Morales, Mundy, Delgado, Yale, Neal, et al., ; Mundy et al., ; Tenenbaum et al., ).…”
Section: Development Of Gf In the First Yearmentioning
confidence: 99%